Search for a light Higgs boson decaying to two gluons or ss[bar] in the radiative decays of [upsilon](1S) - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We search for the decay Υ(1S)→γA0, A0→gg or s¯s, where A0 is the pseudoscalar light Higgs boson predicted by the next-to-minimal supersymmetric Standard Model. We use a sample of (17.6±0.3)×106 Υ(1S) mesons produced in the BABAR experiment via e+e−→Υ(2S)→π+π−Υ(1S). We see no significant signal and set 90%-confidence-level upper limits on the product branching fraction B(Υ(1S)→γA0)⋅B(A0→gg or s¯s) ranging from 10−6 to 10−2 for A0 masses in the range 0.5-9.0 GeV/c2.
Im Titel steht der zweite Buchstabe "s" von "ss" mit einem Oberstrich
Im Titel ist "Ypsilon" (bzw. "upsilon") als griechischer Buchstabe dargestellt
Gesehen am 10.11.2021